Relationship between teacher nonverbal behaviors in the classroom and students' learning - Manalansan, Grettel M. (College of Arts and Letters, University of the Philippines Diliman, 2002)
This thesis examines the relationship of teacher nonverbal communication, specifically non-verbal immediacy behaviors, affective learning, and student perceived cognitive learning. The researcher had the following objectives in mind: 1. to find out if there is a relationship between teacher nonverbal immediacy and affective learning; 2. to find out if a relationship exists between affective learning and cognitive learning; 3. to determine if the relationship of teacher nonverbal immediacy, affective learning, and cognitive learning is linear; and 4. to note the effects, if any, of intervening variables such as teacher gender, class size, and teacher talk time on students' affective learning and cognitive learning.